Noninvasive mechanical destruction of liver tissue and tissue decellularisation by pressure-modulated shockwave histotripsy - Pahk, Ki Joo; Heo, Jeongmin; Joung, Chanmin; Pahk, Kisoo (Frontiers in Immunology, 2023)
Boiling histotripsy (BH) is a promising High Intensity Focused Ultrasound (HIFU) technique that can be used to mechanically fractionate solid tumours at the HIFU focus noninvasively, promoting tumour immunity. Because of the occurrence of shock scattering phenomenon during BH process, the treatment accuracy of BH is, however, somewhat limited. To induce more localised and selective tissue destruction, pressure-modulated shockwave histotripsy (PSH) has recently been proposed in our previous in vitro study as an alternative to or in addition to BH treatment. The aim of the present study was therefore to explore the potential clinical benefits of this newly developed HIFU technique in animal model. In the present study, the effects of PSH on living liver tissue were examined both morphologically and histologically. In the experiments, partially exteriorised in vivo rat’s liver was exposed to a 2.0 MHz HIFU transducer and the animals were sacrificed immediately for analysis. Experimental results showed that a smaller partial mechanical destruction of liver tissue in the form of an oval than that induced by BH was clearly observed at the HIFU focus after the PSH exposure. The smallest PSH lesion created in the liver was measured to be a length of 1.04 mm and a width of 0.87 mm which was 2.04 times in length and 1.11 times in width smaller than a BH lesion produced. This lesion size reduction compared to BH is likely to be due to the absence of shock scattering effect during PSH process which typically occurs in BH. In addition, our experimental results demonstrated the feasibility of (a) controlling the degree of mechanical damage to liver tissue and (b) inducing partial decellularisation effect where liver tissue was partially destructed with intact extracellular matrix (i.e., intact fibrillar collagen) by changing the PSH pulse length. Taken together, these results suggest that PSH can provide higher degrees of treatment accuracy and tissue selectivity than those of BH, leading to the generation of a more localised lesion for the treatment of solid tumours.